Abdominal ultrasound and clinicopathologic findings in 22 cats with exocrine pancreatic insufficiency. (1st October 2021) - Auger, Mylène; Fazio, Constance; Steiner, Joerg M.; Penninck, Dominique G.; Levine, Gwendolyn J.; Griffin, John F.; Springer, Cary M.
Abstract: Background: Awareness of exocrine pancreatic insufficiency (EPI) in cats has increased since the development of an assay for feline trypsin‐like immunoreactivity (fTLI). Ultrasound findings in cats with EPI have only been reported rarely and described as nonspecific. Hypothesis/Objectives: To describe the ultrasonographic findings, clinical signs, and concurrent diseases in cats with EPI. Animals: Twenty‐two client‐owned cats with EPI. Methods: Multicenter retrospective descriptive study including cats with serum fTLI concentration ≤8 μg/L and an abdominal ultrasound examination performed within 6 weeks of fTLI measurement. Sonographic measurements of maximal pancreatic thickness and maximal pancreatic duct diameter as well as ratios of pancreatic duct diameter to pancreatic thickness were obtained. Additional sonographic findings, concurrent conditions, and clinical signs were recorded. Results: The most common clinical sign was weight loss (15/22 cats). Chronic enteropathy was the most common concurrent disease (13/22 cats). In 39% of cats, the pancreas had minimal or no sonographic alterations. Pancreatic duct dilatation (>2.5 mm), pancreatic duct tortuosity with variable diameter, or both were seen in 6/13 cats. The pancreatic parenchyma was subjectively thin in 6 cats. A significant relationship was found between subjectively thin pancreatic parenchyma and increased pancreatic duct size : pancreatic thickness ratio ( P  = .004). Diffuse gastrointestinal dilatation with echogenic content was observed in 8/22 cats. Conclusion: Exocrine pancreatic insufficiency often causes minimal to no sonographic pancreatic changes. Nonetheless, the findings of thin pancreatic parenchyma, pancreatic duct dilatation, or diffuse small intestinal dilatation with echogenic contents in cats with unexplained weight loss or unformed feces should raise clinical suspicion for EPI.